Smart Parenting to Improve Children's Intrapersonal Intelligence (Universitas Negeri Semarang, 2022)
Smart parenting aims to help children develop their abilities optimally, increase their ability to learn, and help them become skilled and thriving individuals. Smart parenting also requires parents to understand children's needs and use appropriate approaches to support children's development. This can include providing emotional support, providing fun learning experiences, and providing practical experiences that help children develop their abilities. The method used is a descriptive method and is accompanied by a qualitative approach. From the results of the At-Taufiq Cimanggis TPA research, it shows that parents' understanding of intrapersonal intelligence of 25 parents of students at TPA At-Taufiq Cimanggis is relatively low, indicated by the response of parents with a percentage of 40% who do not understand intrapersonal intelligence. The type of parenting that is most widely applied by parents of students, namely the type of authoritative parenting with a percentage level of 36%, meaning that parents of TPA At-Taufiq Cimanggis argue that the authoritative type is the most appropriate in developing children's intrapersonal intelligence.